To Study the Science of Application of Dosage and Repetition of Doses in Acute Diseases (Advancements in Homeopathic Research, 2022)
In the present revolution of modern higher antibiotics period giving instant results to the suffering humanity in various diseases with the gift of lot of side effects. Homoeopathy gives two steps ahead simple, medicine in required doses without side effects. The credibility of homeopathic doctor depends upon his ability to manage acute diseases. In chronic cases we will get enough time for prescription. But the scenario is entirely different in acute diseases our prescription should be apt and correct not only with regards to similimum but also with the dosage with required repetitions otherwise patient may land up in further complications or can face aggravations. I will be trying to elaborate the methodology upon which we can improve our performance in acute cases with very high success rate with limited failures as acute diseases are self-limiting disorders which have quick onsets, rapid progressions, and a tendency to develop an immediate crisis. In this research project, every attempt has been made to clarify each component of dosage and repetition when it comes to acute dynamic diseases.
Keywords: Similimum; Acute Dynamic Disease; Dosage; Repetition; aggravations